2006
DOI: 10.1097/01.pec.0000221339.26873.14
|View full text |Cite
|
Sign up to set email alerts
|

Trampoline-related Injury in Children

Abstract: We found no increase in the number of adverse events with morphine pretreatment in ketamine sedations for children. Prospective studies to validate these findings, including an effect of timing of analgesia administration, are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 5 publications
3
29
1
Order By: Relevance
“…4,5,10,39 Probably because of the wall-to-wall trampoline design, there were few falls from trampolines at trampoline parks (Table 2), which may account for the decreased proportion of head and arm injuries at trampoline parks. Lower extremity injuries were common at trampoline parks, and a number of serious lower extremity injuries were reported, including open fractures, dislocations, and other leg fractures necessitating hospital admission.…”
Section: Table 2 Injury Mechanisms Atmentioning
confidence: 99%
“…4,5,10,39 Probably because of the wall-to-wall trampoline design, there were few falls from trampolines at trampoline parks (Table 2), which may account for the decreased proportion of head and arm injuries at trampoline parks. Lower extremity injuries were common at trampoline parks, and a number of serious lower extremity injuries were reported, including open fractures, dislocations, and other leg fractures necessitating hospital admission.…”
Section: Table 2 Injury Mechanisms Atmentioning
confidence: 99%
“…Many literature reviews have concluded that trampolines are not safe for recreational activities and should not be used for recreational purposes at home (Esposito, 2003;Leonard & Joffe, 2009;Nysted & Drogset, 2006;Shankar, Williams, & Ryan, 2006). Rattya and Serlo (2008) reported that the two most effective safety measures, use of a safety net and jumping alone, will only reduce the injury rate by 50%.…”
mentioning
confidence: 96%
“…Many reports have revealed that head and/or neck injuries accounted for 10% to 17% of all trampoline-related injuries, 3,11,12,20 and 0.5% of all trampoline injuries resulted in permanent neurologic damage. 21 Head injuries occurred most commonly with falls from the trampoline.…”
Section: Head and Neck Injuriesmentioning
confidence: 99%
“…11,20 Of these injuries, 1 study revealed that >60% involved the ankle, 20 and approximately three-quarters of ankle injuries were sprains. 6 The upper extremities were injured in 24% to 36% of cases.…”
Section: Extremity Injuriesmentioning
confidence: 99%
See 1 more Smart Citation